The Quantity Effect of Earthworms (Lumbricus Rubellus) and Urea on The NPK Quality of Coffee Husk Waste Compost - Wardani, Kharisma (Journal of Soilscape and Agriculture, 2023)
Utilization of coffee skin waste as compost can reduce the use of chemicals in cultivation. The addition of the two materials to compost with various doses of urea and the number of earthworms (Lumbricus rubellus) is expected to help speed up the process of decomposing coffee husk waste into compost and can increase the nutrient content in the compost. Urea and earthworms are used as decomposition materials and enrich the NPK element in the coffee husk waste compost. The result of making organic fertilizer from coffee husk waste compost is in the form of granules. Granulating is done manually to provide innovation in organic fertilizers. The purpose of this study was to determine the best combination of urea and earthworms in improving the NPK nutrient quality of coffee husk waste compost. Research on coffee husk waste compost was carried out at the Green House and Soil Biology Laboratory, Faculty of Agriculture, University of Jember. The method used was a factorial completely randomized design (CRD) with 2 factors, namely earthworms (Lumbricus rubellus) and urea with 3 levels each. The data obtained were analyzed statistically using Analysis of Variance (ANOVA). If there is a data treatment that shows significantly different results, then the Duncan Multiple Range Test (DMRT) is carried out with a significant level of 5%. The interaction between the number of earthworms (Lumbricus rubellus) and the dose of urea in the composting of coffee husk waste has a very significant effect on several variables, namely; Moisture content, Nitrogen, Phosphorus, Potassium, C-Organic, and C/N ratio values, however, did not significantly affect the temperature and PH variables of coffee husk waste compost.